2020
DOI: 10.3390/en13226051
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Indoor Environmental Quality (IEQ) Model for the Assessment of a Retrofitted Historical Masonry Building

Abstract: Achieving a satisfactory level for indoor environments of historical buildings is an ongoing problem that needs to be solved due to a large demand for deep retrofits in the whole of Europe. The implementation of the indoor environmental quality index (IEQ) to predict an occupant’s satisfaction in thermo-modernized historical buildings is a new concept which is a response to existing needs. In this article, a relevant study is provided with the intention to evaluate the indoor environmental performance of retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Old and historic buildings are mostly energy-inefficient [2,3], and generate more emissions than new buildings [4]. Most of these buildings also suffer from thermal discomfort because when they were built, the main focus was on architecture, durability, mechanical performance, function, and to a much lesser extent, the occupants' comfort and health [5]. Although old and historic buildings are exempt from strict energy-related requirements, retrofitting them has huge potential to provide improved indoor thermal comfort [5] and a reduction in their energy consumption and CO 2 emissions [3,6], which ensures the continued use of these buildings over time and, consequently, their conservation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Old and historic buildings are mostly energy-inefficient [2,3], and generate more emissions than new buildings [4]. Most of these buildings also suffer from thermal discomfort because when they were built, the main focus was on architecture, durability, mechanical performance, function, and to a much lesser extent, the occupants' comfort and health [5]. Although old and historic buildings are exempt from strict energy-related requirements, retrofitting them has huge potential to provide improved indoor thermal comfort [5] and a reduction in their energy consumption and CO 2 emissions [3,6], which ensures the continued use of these buildings over time and, consequently, their conservation [7].…”
Section: Introductionmentioning
confidence: 99%
“…A number of experts stress the indoor overheating produced during the summer due to interior insulation of the envelope [31,32]. Some of them even add that interior insulation also causes permanent moisture, a larger quantity of volatile contaminants, and radon pollution, with no other solution than a mechanical ventilation system [33,34].…”
Section: Improvement Of the Thermal Behavior Of The Envelope Through Better Comprehension Of Thermal Inertiamentioning
confidence: 99%
“…However, other relevant research on different case studies concerning IEQ factors and/or their relationships were found for this review. For the sake of completeness, these pertinent studies are mentioned below: Chiang et al (2001) [74], Frontczak and Wargocki (2011) [75], Kim and de Dear (2012) [76], Catalina and Iordache [77], Sakhare and Ralegaonkar [78], Nimlyat and Kandar (2015) [79], Gadotti and Albatici (2016) [80], Ricciardi and Buratti (2018) [81], Nimlyat (2018) [82], Yang and Moon (2019) [83], Piasecki (2019) [84], Rohde et al (2020) [85], Piasecki et al (2020) [86], and Tang et al (2020) [87].…”
Section: Other Ieq Studiesmentioning
confidence: 99%